PLANEJAMENTO REGIONAL DO TURISMO E DESAFIOS DA REGIÃO TURÍSTICA BAIXADA VERDE: EVIDÊNCIAS DE UMA ANÁLISE LONGITUDINAL - FOGACA, ISABELA; Tavares, Daiane Estacio da Silva; Kalaoum, Fausi (Anais Brasileiros de Estudos Turísticos, 2025)
This article aimed to analyze the stage of implementation of the actions proposed in the Strategic Plan of the Baixada Verde Tourist Region (BV) in two distinct periods: between 2017 and 2020, and between 2021 and 2022, as well as considerations about the structure of the plan itself. BV is a tourist region institutionalized in the Tourism Regionalization Program in 2017, composed of ten municipalities located in the Baixada Fluminense, metropolitan region of Rio de Janeiro. This is a case study with a qualitative and exploratory approach. In addition to documentary analysis, a literature review on public policies and tourism planning was conducted, and data were collected through a questionnaire and form completed by the technical team of each municipality for the respective years, allowing for a longitudinal analysis. The execution of the plan faces significant challenges; there are more than 60 planned actions, most of them in short and medium-term, and little consideration was given to the technical, financial, and human resources available in a newly created region. These results highlight the complexity of regional public management and the importance of continuous adaptation of strategic plans to local conditions and implementation capacity.